Effects of organic or inorganic cobalt, copper, manganese, and zinc supplementation to late-gestating beef cows on productive and physiological responses of the offspring - Marques, R. S. (2016)
Eighty-four multiparous, nonlactating, pregnant Angus × Hereford cows were ranked by pregnancy type (56 AI and 28 natural service), BW, and BCS and allocated to 21 drylot pens at the end of their second trimester of gestation (d 0). Pens were assigned to receive forage-based diets containing 1) sulfate sources of Cu, Co, Mn, and Zn (INR); 2) an organic complexed source of Cu, Mn, Co, and Zn (AAC; Availa 4; Zinpro Corporation, Eden Prairie, MN); or 3) no supplemental Cu, Co, Mn, and Zn (CON). Diets were offered from d 0 until calving and formulated to meet requirements for energy, protein, macrominerals, Se, I, and vitamins. The INR and AAC diets provided the same daily amount of Cu, Co, Mn, and Zn. Cow BW and BCS were recorded and liver samples were collected on d –10 and 2 wk (d 75) before the calving season. Within 3 h after calving, calf BW was recorded, liver samples were collected, and the expelled placenta was retrieved (n = 47 placentas). Calves were weaned on d 283 of the experiment, preconditioned for 45 d (d 283 to 328), transferred to a growing lot on d 328, and moved to a finishing lot on d 440 where they remained until slaughter. Liver Co, Cu, and Zn concentrations on d 75 were greater (P ≤ 0.05) for INR and AAC cows compared with CON cows, whereas INR cows had reduced (P = 0.04) liver Co but greater (P = 0.03) liver Cu compared with AAC cows. In placental cotyledons, Co concentrations were greater (P ≤ 0.05) in AAC and INR cows compared with CON cows, whereas Cu concentrations were increased (P = 0.05) only in AAC cows compared with CON cows. Calves from INR and AAC cows had greater (P < 0.01) liver Co concentrations at birth compared with calves from CON cows. Liver Cu and Zn concentrations at birth were greater (P ≤ 0.05) in calves from AAC cows compared with cohorts from CON cows. Weaning BW was greater (P ≤ 0.05) in calves from AAC cows compared with cohorts from CON cows, and this difference was maintained until slaughter. In the growing lot, calves from AAC cows had reduced (P < 0.01) incidence of bovine respiratory disease compared with CON and INR cohorts. Collectively, these results suggest that feeding the AAC diet to late-gestating beef cows stimulated programming effects on postnatal offspring growth and health compared with the CON diet. Therefore, supplementing late-gestating beef cows with an organic complexed source of Co, Cu, Zn, and Mn instead of no supplementation appears to optimize offspring productivity in beef production systems.